The Sharia Fintech Product on Bank Performance during COVID-19 Pandemic - Laksana, Rio Dhani; Shaferi, Intan; Aydogmus, Ilkay (IKONOMIKA, 2023)
Throughout the COVID-19 epidemic, the Fintech sector has continued to increase access to financial services, especially in developing nations. This study aims to look at how Indonesian Sharia banks' performance is affected by Sharia fintech products (FTPs). Sharia fintech products are a combination of financial and technological innovations that can facilitate customers' transactions and investment processes based on rules and Islamic law so that customers intend to use the Sharia fintech products and then perform well in the bank. This study used 250 Sharia bank customers given self-designed questionnaires as part of our data collection. This study looked at the fictitious relationship, and the results reveal that FTPs have a considerable impact on bank performance, as indicated by the path coefficient and t-value using correlation regression analysis. The study's findings perspectives on how convenient Sharia fintech products (FTPs) are for users. Clients are more receptive to FTPs when they see their use and simplicity in everyday tasks and work. The study's conclusions show that bank performance is positively and significantly impacted by Sharia fintech products of financial transaction platforms (FTPs). Also, the COVID-19 epidemic hastened changes in how people engage with financial services, leading to a hitherto unheard-of demand from poor countries to accelerate their transition to open and safe digital money.